Low-Damage Corn Threshing Technology and Corn Threshing Devices: A Review of Recent Developments - Xinping Li; Wantong Zhang; Shendi Xu; Zhe Du; Yidong Ma; Fuli Ma; Jing Liu (Agriculture, 2023)
Corn is a crucial crop and has a vital application value in many aspects of our lives. Mechanical grain harvesting is the developing direction of corn harvesting technology, with corn threshing as its most imperative procedure. The quality of the threshing device of the corn harvester has a major influence on its damage rate, loss rate, and other parameters. Therefore, it is of great significance to effectively lower the damage rate in the process of corn threshing. This review presents the research progress and the application status of corn threshing technology and corn threshing machinery. The conclusions and suggestions on low-damage corn threshing technology and corn threshing machinery are summarized to provide a reference for the reduction in the damage rate of mechanical grain harvesting and promote the development of mechanical grain harvesting technology.